Introduction to menstrual disturbances in athletes - Loucks, A. B. (Medicine & Science in Sports & Exercise, 2003)
The first symposium on this topic at an annual meeting of ACSM was presented 22 yr ago when the high prevalence of menstrual disorders in athletes was becoming increasingly apparent. The clinical consequences and need for treatment for menstrual disturbances in athletes have been recognized by ACSM through the publication of its 1997 Position Stand on the Female Athlete Triad. This mini-symposium presents an update on recent scientific advances on this topic. The first review in this symposium concentrates on a menstrual disturbance in which the length of the luteal phase is abbreviated and luteal function is suppressed. Such luteal suppression occurs in a large proportion of even the most regularly menstruating athletes. The next two papers summarize what has been learned about the mechanism of these disturbances from prospective experiments that have employed diet, exercise, cold exposure, and pharmacological blockers of metabolic pathways to disrupt menstrual cycles in monkeys and humans as well as estrous cycles and reproductive behavior in hamsters.